Über eine Schnitthyperfläche des Raumes von korrelativen Elementen - Račienė, A. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. А. Рачене, О секущей гиперповерхности пространства коррелятивных элементовA. Račienė, Apie koreliatyvinių elementų erdvės kertamąjį hiperpaviršių